(untitled) (Communications in Mathematical Research, 2021)
For the more general parabolic Monge-Ampère equations defined by the operator F(D^2u + σ(x)), the existence and uniqueness of the admissible solution to the third initial-boundary value problem for the equation are established. A new structure condition which is used to get a priori estimate is established.